Narrative Pedagogy and Cognitive Development: Storytelling for Problem-Solving Skills in Early Childhood through Islamic Literature - Dwiyani Anggraeni; Gina Asri Ruwaida; Azi Matur Rahmi; Putri Ayu Nurkholik; Salsabilla Firdaus (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Problem-solving is a foundational cognitive competency in early childhood development, yet many preschool-aged children exhibit limited capacity to manage interpersonal conflicts and task-related challenges independently. This study aimed to examine the development of problem-solving competencies in early childhood through storytelling-based learning at KB Nurul Athfal, Bekasi, Indonesia. A qualitative descriptive research design was employed, with purposive sampling yielding 20 children aged 3–4 years and 3 classroom teachers as participants. Data were collected through structured observations across six intervention sessions, semi-structured interviews with all three teachers, and documentary evidence. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2014), comprising data condensation, display, and conclusion drawing. Findings revealed meaningful improvements across four behavioral indicators of problem-solving: independent task-attempt behavior increased from 2 to 15 out of 20 children; turn-taking without adult prompting improved from 4 to 16 children; peer cooperation in group tasks increased substantially; and children demonstrated greater capacity to manage physical and academic setbacks. These results suggest that structured storytelling, particularly fable-based narratives emphasizing prosocial values, effectively scaffolds problem-solving and socioemotional development in early childhood. The findings contribute to the growing literature on narrative-based pedagogy in Indonesian early childhood education contexts